114k views
13 votes
If x=2, and y=-3, then xy^2 =

User Sttwister
by
4.4k points

2 Answers

8 votes

Answer:

18

Explanation:

First you must fill input the values into their variable counterparts:

xy^2 turns into: 2 * -3 ^2

Since there isn't a parenthesis around x AND y, the exponent only applies to the y value.

-3 ^2 = 9, so 2 x 9 = 18

xy^2 = 18 if x =2 and y = -3

User Mckbrd
by
5.1k points
2 votes

Answer:

36

Explanation:

If x = 2 and y = -3...

xy^2=

(2)(-3)^2 =

-6^2 =

36

XY times 2=

(-6)(2) =

-12

User Robert Caspary
by
5.1k points